Investigating Hemolytic Activity of Candida Isolates with Two Different Methods - Dogruman-Al, Funda; Kaya, Tugba; Bolat, Sezen; Y. Noral, Mohammad; Aykan, Berna; Aydogan, Sibel; Aksakal, Nur; Kustimur, Semra (Asian Journal of Chemistry, 2010)
The hemolytic activity of Candida isolates with agar and microplate methods were investigated and compared efficiency of these methods to assess relationship between hyphal formation and hemolysis.